Statistical Analysis on Students’ Performance - Afusat, Elepo, Tayo; Samson, Balogun, Oluwafemi (Covenant Journal of Informatics and Communication Technology, 2016)
This research uses Cohen’s Kappa to examine the performance of students in the Faculty of Science, University of Ilorin. The data was collected from eight departments in the faculty and it covers the performance of students measured by their Grade Point Average (GPA) and Cumulative Grade Point Average (CGPA) in both their first and final year between 2000-2006 academic sessions. It is of interest to determine the proportion of students that improved on their performance, dropped from the class of grade point which they started with and those that maintained their performance using psychometrics approach. Also, the strength of agreement that exist between the first and the final year was examined.